Moral psychology - Tenenbaum, Sergio, 1964- (Poznań studies in the philosophy of the sciences and the humanities. New trends in philosophy., 2007)
In recent decades the central questions of moral psychology have attracted renewed interest. Contemporary work on moral motivation and the rationality of moral action has broadened its focus to include a wide array of related issues. New interpretations of historical figures have also contributed to conceptual advances in moral psychology, in a way unparalleled in any other area of philosophy. This volume presents original work from some of the most prominent philosophers currently working on moral psychology, spanning both the historical and the contemporary problem-based approaches.